Comparison of Bone Mineral Density in Common Variable Immunodeficiency and X-Linked Agammaglobulinaemia Patients - Mohebbi, Ali; Azizi, Gholamreza; Tavakolinia, Naeimeh; Abbasi, Farzaneh; Sayarifard, Fatemeh; Karimipour, Mehdi; Kiaee, Fatemeh; Yazdani, Reza; Sadat Ebrahimi, Sareh; Ebrahimi, Mehran; Rafiemanesh, Hosein; Tafaroji, Javad; et al. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2017)
Background: Primary antibody deficiency (PAD) is the most common group of primary immunodeficiency disorders, resulting from different defects in the development and function of B cell lineage. Common variable immunodeficiency (CVID) and X-linked agammaglobulinemia (XLA) are two of the major types of PADs. Optimal growth and subsequently bone health could potentially compromise due to the interference of several factors in PAD with childhood onset. In the present study, our aim was to evaluate bone mineral density (BMD) of patients with CVID and XLA. Methods: BMD of 37 CVID and 19 XLA patients was examined. Total BMD was determined by dual-energy X-ray absorptiometry and the calculated scores were compared internally and externally with age-sex matched and ethnic-specific reference. Related factors associated with bone density including immune-related complications, serum calcium, phosphate, total alkaline phosphatase, 25(OH) vitamin D and parathyroid hormone levels were recorded. Results: The median age at the time of study was 20 years among all patients and was not statistically different between CVID and XLA groups and the mean of body mass index (BMI) was 19.4±4.6 kg/cm2. Thirty-eight (67.9%) of total patients had normal BMD and 18 (32.1%) patients had a low BMD. BMI was positively correlated with BMD at lumbar spine and femoral neck. The number of low BMD patients in CVID (40.5%) group was more than the XLA (15.8%). Conclusion: Beside nutritional, gastrointestinal and infectious complications which are shared in both groups of patients, CVID patients are more prone to alteration of BMD due to association with lymphoproliferative and endocrine diseases. Therefore routine evaluation of bone density and treatment adjustment should be considered in all PAD patients particularly in CVID patients.
Keywords: Bone mineral density